Start reaction time and performance at the sprint events in World Athletic Championships - Pilianidis, T. H.; Mantzouranis, N.; Kasabalis, A (Journal of Quantitative Analysis in Sports, 2012)
The aim of this study was to determine the relationship between the start reaction time and the performance in men sprinters who participated at the World Indoor Athletics Championships. This study's sample was 161 athletes (n=161) who participated in the final races of 100m (n=52), 200m (n=55) and 110m hurdles (n=54) in Athens 1997, Seville 1999, Edmonton 2001, Paris 2003, Helsinki 2005, Osaka 2007 and Berlin 2009 IAAF World Athletics Championships. The evaluation of start reaction time as well as the sprinters' performance was based on the official published reports of International Association of Athletics Federations (IAAF). The MANOVA showed that significant differences between athletes' start reaction time were identified only in 110m hurdles sprint event [F(6.43)=4.70], p<0.001. The post hoc comparisons reported that the start reaction time (125ms) in the 110m hurdles final in Athens 1997 was the best recorded in all sprint final races during the evaluated Championships from 1997 and on. Because the start reaction times in all final sprint races were recorded better in Athens 1997 than after the Paris 2003 Championships leads to the conclusion that the new IAAF false start rule has a negative effect in top-level athletes' start reaction time